Pentingnya pendidikan akhlak dalam mewujudkan sikap terpuji di Pondok Pesantren SMP Sabilurrosyad - Arifuqin, Muhammad Amirul; Faruq, Alfian Haikal; Muttaqin, M. Imamul (Maliki Interdisciplinary Journal, 2024)
Moral education is something that must be studied by all groups, especially as recently there has been a lot of moral decline in society. So many groups are intensively carrying out moral education, one of which is Islamic boarding schools. Moral education itself has many branches, but we focus the discussion on attitudes of justice, pleasure, good deeds, unity and harmony. Because when moral education is successfully implemented, a harmonious atmosphere will be created.